Pelestarian Kesenian Melalui Tradisi Saparan - Maulana, Indra; Umami, Zahrotul (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
Local culture inherent in Indonesian society has undergone changes in the Era of Society 5.0. The teenage generation already understands the sense of nationalism but they themselves are aware of the current of modernization that makes them have to adapt to be more modern and unconsciously leave local culture. This results in significant changes in people's lives, especially the culture of the community itself. This study aims to determine the Saparan tradition as a communication medium to preserve the arts, especially in the context of local arts in Tajuk village. The research method used is descriptive qualitative with a phenomenological approach with data collection techniques in the form of data collection techniques: interviews, observations, documentation. The results of the study indicate that the Saparan Tradition is a strong cultural communication medium in building and maintaining the identity of the local community. The Saparan Tradition has an important role in intercultural communication, especially in terms of preserving local arts. In addition, it was found that the Saparan tradition is a bridge for the process of exchanging messages between individuals or groups from different cultural backgrounds. This study shows that Saparan is also an effective intercultural communication medium, where the exchange of values, symbols, and cultural practices occurs not only between local residents, but also between local communities and visitors from outside the area. And provides implications for the preservation of local arts.